2017
DOI: 10.1371/journal.pone.0170283
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus SrrAB Regulatory System Modulates Hydrogen Peroxide Resistance Factors, Which Imparts Protection to Aconitase during Aerobic Growth

Abstract: The SrrAB two-component regulatory system (TCRS) positively influences the transcription of genes involved in aerobic respiration in response to changes in respiratory flux. Hydrogen peroxide (H2O2) can arise as a byproduct of spontaneous interactions between dioxygen and components of respiratory pathways. H2O2 damages cellular factors including protein associated iron-sulfur cluster prosthetic groups. We found that a Staphylococcus aureus strain lacking the SrrAB two-component regulatory system (TCRS) is sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 97 publications
0
30
0
Order By: Relevance
“…aureus increases the transcription of genes necessary to metabolize reactive oxygen species (ROS) when cultured under high aeration, suggesting that endogenous ROS accumulates under these growth conditions (33). Consequently, S. aureus strains deficient in the maturation of Fe-S proteins or scavenging endogenously produced ROS display severe defects in AcnA activity when the dioxygen tension is increased (19).…”
Section: Resultsmentioning
confidence: 99%
“…aureus increases the transcription of genes necessary to metabolize reactive oxygen species (ROS) when cultured under high aeration, suggesting that endogenous ROS accumulates under these growth conditions (33). Consequently, S. aureus strains deficient in the maturation of Fe-S proteins or scavenging endogenously produced ROS display severe defects in AcnA activity when the dioxygen tension is increased (19).…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, the Δ ytfE strain is sensitive to other antimicrobial compounds generated within host tissues, possibly by the generation of a variety of reactive nitrogen species (RNS) as a consequence of NO reaction with reactive oxygen species (ROS) or other compounds. Upregulation of ytfE following hydrogen peroxide-mediated damage of Staphylococcus aureus indicates that YtfE may play a broad role in repair, instead of just a response to nitrogen stress (44, 45). Additional studies in E. coli also suggest that YtfE repairs Fe-S cluster proteins damaged by hydrogen peroxide (13, 46-49).…”
Section: Discussionmentioning
confidence: 99%
“…RNA extractions and real-time quantitative PCR. The abundances of RNAs were determined using a previously described cDNA library (35,53). Briefly, cells were cultured in capped microcentrifuge tubes at a headspace-to-volume (H/V) ratio of 0.…”
Section: Methodsmentioning
confidence: 99%
“…ClpCP is required for optimal growth in a medium that only supports respiratory growth. SrrAB regulates aerobic respiration, and the data presented suggested that a ΔclpC strain may be deficient in oxidative phosphorylation and tricarboxylic acid (TCA) cycle activity (35,36). This prompted us to test the hypothesis that ClpC positively influences respiratory growth.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation